2011
DOI: 10.1146/annurev-med-042909-093734
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia: Will Blocking Inflammation Tame the Disease?

Abstract: Biliary atresia is the most common cholangiopathy of childhood. With complete obstruction of segments or the entire length of extrahepatic bile ducts, the timely pursuit of hepatoportoenterostomy is the best strategy to restore bile drainage. However, even with prompt surgical intervention, ongoing injury of intrahepatic bile ducts and progressive cholangiopathy lead to end-stage cirrhosis. The pace of disease progression is not uniform; it may relate to clinical forms of disease and/or staging of liver pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 64 publications
4
72
0
Order By: Relevance
“…The immune system plays a major role in the progressive fibrosis and obliteration of bile ducts in BA [21]. Release of proinflammatory cytokines from activated immune cells permanently damages bile ducts and causes biliary destruction, followed by fibrosis, producing the atresia phenotype [22].…”
Section: Inhibition Of Notch Signaling Reduces Inflammatory Cytokinesmentioning
confidence: 99%
“…The immune system plays a major role in the progressive fibrosis and obliteration of bile ducts in BA [21]. Release of proinflammatory cytokines from activated immune cells permanently damages bile ducts and causes biliary destruction, followed by fibrosis, producing the atresia phenotype [22].…”
Section: Inhibition Of Notch Signaling Reduces Inflammatory Cytokinesmentioning
confidence: 99%
“…Although the etiology is largely undefined, patient-and animal-based experiments point to a key role of the innate and adaptive immune responses in the pathogenesis of bile duct injury and obstruction (1). Studies using an experimental model of rhesus rotavirus-induced (RRV-induced) biliary atresia in newborn BALB/c mice have shown that the mechanisms of bile duct injury begins with the activation of DCs and NK cells, which target the bile duct epithelium (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of etiology, biliary atresia seems to be a heterogeneous condition in which environmental factors can act both in the early intrauterine period (embryonic form) and in the perinatal period (isolated form) [13][14][15][16] . This study showed that the conception of a patient with BA was 84% less likely if this condition was diagnosed in winter, suggesting a seasonal influence on BA etiology, although season at birth was not associated with the occurrence of BA.…”
Section: Discussionmentioning
confidence: 99%